Bilateral coronoid hyperplasia causing limited mouth opening: A report of two cases - Pooja Jain; Supriya Balchim Gabhale; Sonali Kadam; Prakhar Agrawal (Wolters Kluwer Medknow Publications, 2018)
Bilateral hyperplasia of the coronoid process of the mandible is an unusual entity which often presents with limited mouth opening. Thorough clinical and radiographic examination can help in the diagnosis and the treatment planning of this condition. This article consists of a case report of two patients. The patient in each case, presented with a reduced mouth opening, and when subjected to further investigations, was diagnosed with bilateral coronoid hyperplasia.